Pengaruh Pola Konsumsi Makanan Ultra-Proses terhadap Risiko Sindrom Metabolik pada Usia Produktif - Satria Kurniawan; Samsul Bahri; Mariam Annisa (Gema Cendekia Institute, 2026)
The rapid expansion of digital communication technologies has transformed the way young people interact, form relationships, and experience social connection. While digital platforms offer unprecedented opportunities for communication and networking, emerging evidence suggests that intensive online engagement may also contribute to new forms of social isolation. This study examines the phenomenon of digital loneliness among young adults by analyzing patterns of digital interaction, perceived social connection, and the role of digital literacy. The research adopts a quantitative approach using survey data collected from young individuals who actively use social media and other digital communication platforms. Data analysis focuses on identifying relationships between frequency of digital interaction, quality of online communication, and perceived feelings of loneliness. The findings indicate that high levels of digital engagement do not necessarily translate into meaningful social relationships. Many respondents report frequent online communication but experience limited emotional depth in their interactions. Algorithm driven content exposure and constant social comparison further intensify feelings of isolation despite apparent social connectivity. The study also reveals that digital literacy plays a crucial moderating role. Individuals with higher levels of digital literacy demonstrate stronger awareness of platform dynamics, better control over digital consumption patterns, and a greater ability to develop purposeful online interactions. These results highlight the importance of strengthening digital literacy as a strategy to reduce the negative social consequences of intensive digital media use. Effective digital engagement requires not only technical competence but also critical awareness of how digital environments shape social experiences. Strengthening these competencies can support healthier patterns of communication and help reduce the risk of digital loneliness among young adults.